Ajatuksia Yrittäjyysyliopistosta: Academics and entrepreneurs – true or false dichotomy? - Inna Kozlinska (Turun yliopisto, 2026)
As an academic in the field of entrepreneurship, I cannot help thinking if I should become an entrepreneur myself. In Finland and elsewhere, popularity of entrepreneurship as a career path increased spectacularly in the last couple of decades. Entrepreneurship is gradually becoming transdisciplinary in universities of various kinds. And universities in Europe are making a conscious strategic shift towards becoming more entrepreneurial, to better serve society and economy. The universities are actively working on entrepreneurship strategies, but is the marriage of being an academic and entrepreneur made in heaven?